Nitrogen uptake over entire root systems of tree seedlings. (3rd March 2014) - Hawkins, B.J.; Robbins, S.; Porter, R.B.
Abstract : Uptake of nitrogen (N) by sequential root regions in six tree species was measured in roots of 16- to 26-month-old seedlings at 50 and 1500 µM NH4 NO3 concentration, at the cell level using oscillating microelectrodes and at the root region level using enriched 15 N application. Our objective was to determine the root regions making the greatest contribution to total N uptake in each species as measured by the two contrasting techniques. White and condensed tannin zones were the regions with the smallest surface area in all species, but these zones often had the highest net flux of NH4 + and NO3 − . For most species, little variation was found among root regions in N flux calculated using a 15 N mass balance approach, but where significant differences existed, high N flux was observed in white, cork or woody zones. When N fluxes measured by each of the two methods were multiplied by the estimated surface area or biomass of each root region, the effect of root region size had the greatest influence on regional N uptake. Root regions of greatest overall N uptake were the cork and woody zones, on average. Total N uptake may thus be greatest in older regions of tree seedling roots, despite low rates of uptake per unit area.